2019
DOI: 10.1002/adma.201904058
|View full text |Cite
|
Sign up to set email alerts
|

NaCl Nanoparticles as a Cancer Therapeutic

Abstract: Mammalian cells sustain low ratios of intracellular to extracellular sodium and chloride, and high ratios of potassium. [1] These asymmetric ionic gradients are critical to cell functions, driving essential cellular processes including the transport of amino acids, maintenance of cellular pH, and control of cell volume. [2] Lowering the extracellular concentrations of sodium and chloride, for instance by immersing cells in a hypotonic solution, causes cytoskeleton destruction, cell cycle arrest, and cell lysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
112
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(116 citation statements)
references
References 49 publications
0
112
0
Order By: Relevance
“…The XRD pattern of CaBPs showed that the overall crystalline structure of CaBPs was preserved because the typical diffraction peaks were consistent with those of the standard orthorhombic BP (PDF#76-1959, Figure S8, Supporting information). The Raman scattering spectrum of CaBPs showed the three prominent Raman peaks of BPs, A 1 g , B 2g , and A 2 g , [19] with slight red-shifts compared to BPs (Figure 1i). All in all, although BPs were covered by the CaP layer, CaP mineralization did not alter the overall structure and physical properties of BPs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The XRD pattern of CaBPs showed that the overall crystalline structure of CaBPs was preserved because the typical diffraction peaks were consistent with those of the standard orthorhombic BP (PDF#76-1959, Figure S8, Supporting information). The Raman scattering spectrum of CaBPs showed the three prominent Raman peaks of BPs, A 1 g , B 2g , and A 2 g , [19] with slight red-shifts compared to BPs (Figure 1i). All in all, although BPs were covered by the CaP layer, CaP mineralization did not alter the overall structure and physical properties of BPs.…”
Section: Resultsmentioning
confidence: 99%
“…Based on above investigations, a key question now was finding out whether dissipation of MMP derived from direct interactions between CaBPs and cells or intracellular ionic osmolarity changes after CaBPs degradation. Mitochondria were isolated and the CaBPs signals in the mitochondria were detected by monitoring the characteristic A 1 g Raman peak of BPs. [9a,27] Obvious Raman signals were observed from CaBPs in the mitochondria after incubation for 24 h ( Figure S18a, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…68 The NaCl nanoparticles enter the cell through endocytosis, bypassing the physiological iontransport system, and release Na + and Cl − ions inside cancer cells because of their high solubility, causing a surge of osmolarity and rapid cell lysis. 66 All of these reports could support the efforts of scientists to develop self-therapeutic nanomaterials with future applications in cancer therapy.…”
Section: Other Self-therapeutic Nanomaterialsmentioning
confidence: 85%
“…[78] Interestingly,N aCl nanoparticles also selectively killed tumor cells and boosted antitumor immunity. [79] Figure 7. (a) Schematic representation of an in situ sprayed bioresponsivef ibrin gel on apostsurgical tumor bed.…”
Section: Other Materialsmentioning
confidence: 99%